Summary Proceedings of the Fifty-Fourth Annual Meeting of the Board of Governors, September 28-30, 1999. (Summary Proceedings; 54th Annual Meeting, 1999, 1999)
This annual publication is a record of the IMF's Annual Meeting and contains the opening and closing addresses of the Chairman of the Board of Governors, presentation of the Annual Report by the Managing Director, statements of Governors, committee reports, resolutions, and a list of delegates. Usually published in March.